2019
DOI: 10.1088/1361-648x/ab41b5
|View full text |Cite
|
Sign up to set email alerts
|

Local entanglement and string order parameter in dimerized models

Abstract: In this letter, we propose an application of String Order Parameter (SOP), commonly used in quantum spin systems, to identify symmetry-protected topological phase (SPT) in fermionic systems in the example of the dimerized fermionic chain. As a generalized form of dimerized model, we consider a one-dimensional spin-1/2 XX model with alternating spin couplings. We employ Jordan-Wigner fermionization to map this model to the spinless Su-Schrieffer-Heeger fermionic model (SSH) with generalized hopping signs. We de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
(90 reference statements)
0
3
0
Order By: Relevance
“…STRING database can analyze the interaction relationship between some proteins [ 23 25 ]. cytoHubba can identify hub objects and subnetworks from a complex interactome.…”
Section: Discussionmentioning
confidence: 99%
“…STRING database can analyze the interaction relationship between some proteins [ 23 25 ]. cytoHubba can identify hub objects and subnetworks from a complex interactome.…”
Section: Discussionmentioning
confidence: 99%
“…[25] can also be transformed into a spin model in a finite length lattice with open boundary condition. Upon using the Jordan-Wigner transformation [49]:…”
Section: A Lattice Modelmentioning
confidence: 99%
“…den Nijs and Rommelse first showed that the SOP witnesses the hidden Néel order of the Haldane phase of the spin-1 AKLT model [76]. More recent work has extended the use of SOPs in the analysis of topological phases also to bosonic and fermionic systems [77][78][79][80][81]. Recently, within the context of high T c superconductivity, SOPs have been used to theoretically study the topological phases diagram of the t − J model [82].…”
Section: String Order Parametermentioning
confidence: 99%